Positive antiphase boundary domain wall magnetoresistance in Fe3O4 (110) heteroepitaxial films - SHVETS, IGOR; ARORA, SUNIL (My University, 2011)
We observe a strong crystallographic direction dependence on the low-field magnetoresistance (MR) behavior of the epitaxial Fe3O4 (110) films grown on MgO (110) substrates. The sign of MR is positive when the current and field are parallel to [001], whereas along the [1?10] direction its sign is negative, similarly to that commonly observed for (100) oriented Fe3O4 films. We relate this effect to the presence of antiphase boundaries (APB) and subsequent reduction in the width of canted spin structure in its vicinity, due to the hard axis behavior of Fe3O4 (110) films along this crystallographic direction. At fields greater than the anisotropy field, usual negative MR behavior related to a reduction in spin scattering at the APBs is observed. An analytical model based on the half-infinite spin chains across the APBs is provided to show that the positive MR is due to the domain walls along APBs. The temperature and film thickness dependency of the APB domain wall magnetoresistance is discussed.
PUBLISHED
9p
Keywords: Atomic, molecular and chemical physics; Magnetic properties and materials; Thin Films; Nanoscience & Materials